IMPACT OF FARMER FIELD SCHOOL APPROACH ON THE COMPETENCY OF THE FARMERS - M. Hussain; F. Rehman2; I. Bibi; S. Khalid; S. Khalid (Journal of Animal and Plant Sciences, 2017)
The present study was conducted in the Lahore district to analyze the impact of Farmer Field School (FFS) approach on the competency of the farmers. The population for the study was consisted of both the registered and non-registered farmers under the FFS approach in the public sector in Lahore district. A sample was drawn from the entire population of twenty four FFSs of Lahore district, by using simple random sampling technique. Out of twenty four, eight FFSs were selected randomly and from each FFS eight registered farmers was interviewed, thus the total sample size of registered farmers was sixty four. The non-registered farmers (non-member farmers) were also interviewed to make the research result more authenticated. Thus the number of non-registered farmers was also sixty four. Hence the total sample frame was 128 farmers. The data were collected with the help of a pre-tested and validated interview schedule especially designed for this purpose. The data were analyzed by using computer software Statistical Package for Social Sciences (SPSS). Analysis of the data shows that the farmers’ competency in the conduction of agricultural activities land preparation and direct sowing were top in rank order in member and non-members’ farmers. While on the other hand member farmers’ competency in controlling harmful insects was at the bottom in rank order, however, non-members had lowest competency in conduction of Agro Ecosystem Analysis (AESA) activity. T-test clearly indicates that all aspects of competency in undertaking the agricultural activities had significant difference in favour of member farmers. It means member farmers had more competency in agriculture as compared to non-member farmers.
Keywords: Farmer Field School; competency; farmers